Biological effects in normal human fibroblasts following chronic and acute irradiation with both low- and high-LET radiation - Anello, Pasqualino; Esposito, Giuseppe (Frontiers in Public Health, 2024)
Introduction Radiobiological studies at low dose rates allow us to improve our knowledge of the mechanisms by which radiation exerts its effects on biological systems following chronic exposures. Moreover, these studies can complement available epidemiological data on the biological effects of low doses and dose rates of ionizing radiation. Very few studies have simultaneously compared the biological effects of low- and high-LET radiations at the same dose rate for chronic irradiation. Methods We compared, for the first time in the same experiment, the effects of chronic (dose rates as low as 18 and 5 mGy/h) and acute irradiations on clonogenicity and micronucleus formation in AG1522 normal human skin fibroblasts in the confluent state exposed to doses of low- and high-LET radiation (gamma rays and alpha particles) to investigate any differences due to the different radiation quality and different dose rate (in the dose range 0.006–0.9 Gy for alpha particles and 0.4–2.3 Gy for gamma rays). Results As expected, alpha particles were more effective than gamma rays at inducing cytogenetic damage and reduced clonogenic cell survival. For gamma rays, the cytogenetic damage and the reduction of clonogenic cell survival were greater when the dose was delivered acutely instead of chronically. Instead, for the alpha particles, at the same dose, we found equal cytogenetic damage and reduction of clonogenic cell survival for both chronic and acute exposure (except for the highest doses of 0.4 and 0.9 Gy, where cytogenetic damage is greater at a low dose rate). Conclusion The results of this study may have an impact on space and terrestrial radioprotection of humans at low doses and low dose rates, on biodosimetry, and on the use of ionizing radiation in medicine. These results also provide insights into understanding damage induction and cell reaction mechanisms following chronic exposure (at dose rates as low as 18 and 5 mGy/h) to low- and high-LET radiation.